-6(-5+3)+8n=18+2n

Simple and best practice solution for -6(-5+3)+8n=18+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-5+3)+8n=18+2n equation:



-6(-5+3)+8n=18+2n
We move all terms to the left:
-6(-5+3)+8n-(18+2n)=0
We add all the numbers together, and all the variables
8n-(2n+18)-6(-2)=0
We add all the numbers together, and all the variables
8n-(2n+18)+12=0
We get rid of parentheses
8n-2n-18+12=0
We add all the numbers together, and all the variables
6n-6=0
We move all terms containing n to the left, all other terms to the right
6n=6
n=6/6
n=1

See similar equations:

| 11h-6h=15 | | 3+7x2=x | | -4j=20,8 | | u+4/5=61/3 | | -140=-7x/1 | | 5x-8=3.5 | | -85=5v/1 | | 4n+1=1 | | 4=24-5n | | -13x/1=26 | | y=-119y= | | 3x+10=3.5 | | 192=-12r/1 | | 2(3r-6)-7(1+5r)=r+6-5r | | 9b/1=-36 | | 9y-2=5 | | 432=16v | | n=124n= | | 5X+20y=-15 | | 9x−4=9(x}−1)+14 | | -0.4(x3)=4 | | -6x-9=3x+36 | | -16x/1=-100 | | 9x−4=9(x−1)+14 | | w+2/5=-1/6 | | 2w^2+16w=-20 | | -8u+13.9=1.1 | | 2n=308 | | 20v^2-10=-46v | | -3.1=u÷5+9.4 | | (3y+11)=(4y-22) | | 30r=120 |

Equations solver categories